The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-35409-0
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni bile exposure influences outer membrane vesicles protein content and bacterial interaction with epithelial cells

Abstract: Campylobacter jejuni is a prevalent human pathogen and a major cause of bacterial gastroenteritis in the world. In humans, C. jejuni colonizes the intestinal tract and its tolerance to bile is crucial for bacteria to survive and establish infection. C. jejuni produces outer membrane vesicles (OMVs) which have been suggested to be involved in virulence. In this study, the proteome composition of C. jejuni OMVs in response to low concentration of bile was investigated. We showed that exposure of C. jejuni to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 77 publications
3
23
1
Order By: Relevance
“…Both the mlaA mutant OMVs and wild-type ST-OMVs had comparable diameters. This is in contrast to data from a recent study (Taheri et al, 2018) which did not observe increased OMV production in response to ox bile. Ox bile was used to represent a mixture of bile salts, similar to what would be found in the gut, whereas ST alone was used in this study, a single component of human bile.…”
Section: Discussioncontrasting
confidence: 99%
“…Both the mlaA mutant OMVs and wild-type ST-OMVs had comparable diameters. This is in contrast to data from a recent study (Taheri et al, 2018) which did not observe increased OMV production in response to ox bile. Ox bile was used to represent a mixture of bile salts, similar to what would be found in the gut, whereas ST alone was used in this study, a single component of human bile.…”
Section: Discussioncontrasting
confidence: 99%
“…[185] indirectly confirmed the abovementioned findings by Taheri et al. [184] using bile salt sodium taurocholate. After treatment with this bile salt, C. jejuni outer MV production increased, with increased MVs‐associated proteolytic activity as a consequence.…”
Section: Bacterial Extracellular Vesiclessupporting
confidence: 78%
“…According to Taheri et al [176] composition of the C. jejuni MVs depends on growth temperature and it has implications for the outcome of colonization and pathogenicity of this bacterium in different hosts. Elmi et al [185] indirectly confirmed the abovementioned findings by Taheri et al [184] using bile salt sodium taurocholate. After treatment with this bile salt, C. jejuni outer MV production increased, with increased MVs-associated proteolytic activity as a consequence.…”
Section: Gram Negative Bacteriamentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, a similar route of MV formation has been suggested in Stenotrophomonas maltophilia, as production of O-IMVs and phages was detected in response to ciprofloxacin stress (Devos et al, 2017). The involvement of cell lysis in MV formation would explain why inner membrane and cytoplasmic components are detected in many proteomic analyses of OMV fractions (Kulkami et al, 2014;Olaya-Abril et al, 2014;Oliver et al, 2017;Avila-Calderón et al, 2018;Taheri et al, 2018).…”
Section: Composition and Biogenesis Of Bacterial Mvsmentioning
confidence: 62%